2020
DOI: 10.3390/ph13040054
|View full text |Cite
|
Sign up to set email alerts
|

Improved Surface Display of Human Hyal1 and Identification of Testosterone Propionate and Chicoric Acid as New Inhibitors

Abstract: Degradation of high molecular weight hyaluronic acid (HA) in humans is mainly catalyzed by hyaluronidase Hyal1. This enzyme is involved in many pathophysiological processes and therefore appears an interesting target for drug discovery. Until now, only a few inhibitors of human Hyal1 are known due to obstacles in obtaining active enzymes for inhibitor screening. The aim of the present work was to provide a convenient enzyme activity assay and show its feasibility by the identification of new inhibitors. By aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have demonstrated that the surface of cancer cells over-express the CD44 receptors on their surface, to which HA strongly binds [ 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, HA can be utilized as a target ligand for tumor-targeted drug delivery [ 31 , 32 , 33 , 34 , 35 ]. The structure of HA can be modified to produce a variety of derivatives, which not only maintains its stability, but also enhances its bio-compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the surface of cancer cells over-express the CD44 receptors on their surface, to which HA strongly binds [ 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, HA can be utilized as a target ligand for tumor-targeted drug delivery [ 31 , 32 , 33 , 34 , 35 ]. The structure of HA can be modified to produce a variety of derivatives, which not only maintains its stability, but also enhances its bio-compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that chicoric and caftaric acid have excellent antihyaluronidase activity [ 33 ]. Furthermore, chicoric acid, the main ingredient of TPA-opt, was found to inhibit human hyaluronidase 1, the enzyme that degrades high molecular weight hyaluronic acid [ 34 ]. Other caffeic acid derivatives may also add to the beneficial effect on wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…In a study, Lengers and team found chicoric acid (IC 50 = 171 μM) and testosterone propionate (IC 50 = 124 ± 1.1 μM) as strong inhibitors of Hyal1 expressed over the surface of Escherichia coli F470 which was comparable to that of glycyrrhizic acid (IC 50 = 177 μM) [68].…”
Section: Terpenes and Steroidsmentioning
confidence: 98%